Sensor Systems and Software First International ICST Conference, S-CUBE 2009, Pisa, Italy, September 7-9, 2009, Revised Selected Papers - Hailes, Stephen; Sicari, Sabrina; Roussos, George; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the First International ICST Conference, S-CUBE 2009, held in Pisa, Italy, in september 2009. The 16 contributions published in this volume were carefully selected from 45 submitted works in a rigorous peer-reviewed process. In addition to this 3 distinguished researchers were asked to contribute 3 invited papers. The papers examine research challenges facing system development and software support for wireless sensor networks (WSNs). Currently, wireless sensor networks introduce innovative and interesting application scenarios that may support a large amount of different applications including environmental monitoring, disaster prevention, building automation, object tracking, nuclear reactor control, fire detection, agriculture, healthcare, and traffic monitoring. The widespread acceptance of these new services can be improved by the definition of frameworks and architectures that have the potential to radically simplify software development for wireless sensor network based applications. The aim of these new architectures is to support flexible, scalable programming of applications based on adaptive middleware. As a consequence, WSNs require novel programming paradigms and technologies. Moreover the design of new complex systems, characterized by the interaction of different and heterogeneous resources, will allow the development of innovative applications that meet high performance goals. Hence, WSNs require contributions from many fields such as embedded systems, distributed systems, data management, system security and applications.
Applying Complex Event Processing and Extending Sensor Web Enablement to a Health Care Sensor Network Architecture -- Turn-Based Gesture Interaction in Mobile Devices -- A Large-Scale Wireless Network Approach for Intelligent and Automated Meter Reading of Residential Electricity -- Weak Process Models for Attack Detection in a Clustered Sensor Network Using Mobile Agents -- Key Establishment Using Group Information for Wireless Sensor Networks -- A Forward and Backward Secure Key Management in Wireless Sensor Networks for PCS/SCADA -- Analysis of Channel Access Delay of Slotted CSMA/CA in a WSN -- Accurate Analysis of IEEE 802.15.4 Slotted CSMA/CA over a Real-Time Wireless Sensor Network -- Physical Characterization of Acoustic Communication Channel Properties in Underwater Mobile Sensor Networks -- A Code Generator for Distributing Sensor Data Models -- Integer-Based Optimisations for Resource-Constrained Sensor Platforms -- ProSe: A Programming Tool for Rapid Prototyping of Sensor Networks -- Energy-Aware Dynamic Route Management for THAWS -- All Roads Lead to Rome: Data Highways for Dense Wireless Sensor Networks -- Sensor Data Fusion for Activity Monitoring in Ambient Assisted Living Environments -- Trade-off Analysis of a MAC Protocol for Wireless e-Emergency Systems -- An Underwater Robotic Network for Monitoring Nuclear Waste Storage Pools -- Evaluation of the Impact of the Topology and Hidden Nodes in the Performance of a ZigBee Network -- Coordinated Sleeping for Beaconless 802.15.4-Based Multihop Networks.
Keywords: Computer science; Computer network architectures; Computer Communication Networks; Information storage and retrieval systems; Information systems; Computer Science; Computer Systems Organization and Communication Networks; Computer Communication Networks; Information Systems Applications (incl.Internet).; Computer Applications; Information Storage and Retrieval; Computers and Society